Adhesive for circuit connection, connection structure, and method for producing the connection structure
The use of a circuit connection adhesive with alicyclic epoxy compounds and specific onium salts in thermocompression bonding addresses the issue of high resistance in low-temperature bonding, ensuring durable and reliable electrical connections.
Patent Information
- Application Number
- JP2020198510
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2020-11-30
- Publication Date
- 2025-01-07
- Estimated Expiration
- 2040-11-30
AI Technical Summary
Conventional circuit connection adhesives result in increased connection resistance when thermocompression bonding is performed at low temperatures and short times, especially with low heat-resistant substrates like plastic or thin film glass, which is detrimental to the yield and reliability of circuit connections.
A circuit connection adhesive comprising a cationically polymerizable compound, thermal cationic polymerization initiator, and conductive particles, specifically using an alicyclic epoxy compound and an onium salt with a particular anion, which enhances low-temperature curability and suppresses excessive conductive particle flow during bonding.
The adhesive achieves a connection structure with significantly reduced resistance between electrodes, maintaining low resistance even under high temperature and humidity conditions, and ensures durable and reliable electrical connections.
Smart Images

Figure 0007608801000012 
Figure 0007608801000013 
Figure 0007608801000014
Abstract
Description
[Technical field]
[0001] The present invention relates to an adhesive for circuit connection, a connection structure, and a method for producing a connection structure. [Background technology]
[0002] Conventionally, various adhesive materials have been used for circuit connection. For example, a circuit connection adhesive in which conductive particles are dispersed in the adhesive is used as an adhesive material (circuit connection material) for electrically connecting a TCP (Tape Carrier Package) or a COF (Chip On Flex) on which a semiconductor for driving a liquid crystal display (LCD) is mounted and an LCD panel, or a TCP or COF and a printed wiring board.
[0003] Furthermore, even when mounting a semiconductor face-down directly on an LCD panel or printed wiring board, flip-chip mounting, which is advantageous for thin film and narrow pitch connection, is adopted rather than the conventional wire bonding method, and here too, a circuit connection adhesive in which conductive particles are dispersed is used as the circuit connection material (see, for example, Patent Document 1). [Prior art documents] [Patent documents]
[0004] [Patent Document 1] Japanese Patent Application Publication No. 1-251787 Summary of the Invention [Problem to be solved by the invention]
[0005] Usually, the connection between circuit members using a circuit connection adhesive is performed by heating and pressing the circuit members together (thermocompression bonding) with the circuit connection adhesive interposed between them. The heating temperature during thermocompression bonding varies depending on the type of circuit member, but for example, when a member having a substrate with poor heat resistance such as a plastic substrate or a thin-film glass substrate is used as the circuit member, thermocompression bonding is performed at a temperature of about 130 to 160°C.
[0006] In recent years, from the viewpoints of suppressing damage to low heat-resistant members around the bonding points and improving yields, there has been a demand for further lowering the temperature during thermocompression bonding and shortening the bonding time, and for example, there is a demand for circuit connection by thermocompression bonding at less than 130° C. for 5 seconds or less. However, as a result of the studies by the present inventors, it has become clear that when a conventional circuit connection adhesive is used, the connection resistance value between opposing electrodes increases during thermocompression bonding under the above-mentioned conditions.
[0007] Therefore, a main object of the present invention is to provide an adhesive for circuit connection, which can obtain a connection structure having sufficiently low connection resistance between opposing electrodes by thermocompression bonding at low temperature in a short time. [Means for solving the problem]
[0008] The present inventors have found that an onium salt having an anion represented by the following formula (1) specifically exhibits an effect of improving low-temperature curing property when combined with an alicyclic epoxy compound, and have completed the present invention. [ka]
[0009] That is, one aspect of the present invention relates to an adhesive for circuit connection as described in [1] below.
[0010] [1] An adhesive for circuit connection comprising a cationic polymerizable compound, a thermal cationic polymerization initiator, and conductive particles, wherein the cationic polymerizable compound contains an alicyclic epoxy compound, and the thermal cationic polymerization initiator contains an onium salt having an anion represented by the following formula (1): [ka]
[0011] According to the circuit connection adhesive of the above aspect, a connection structure having a sufficiently low connection resistance between opposing electrodes can be obtained by thermocompression bonding at a low temperature in a short time. The reason why such an effect is obtained is not clear, but it is presumed that the circuit connection adhesive of the above aspect has excellent low-temperature curing properties due to the combination of an alicyclic epoxy compound and an onium salt having an anion represented by the above formula (1), so that excessive flow of the conductive particles during thermocompression bonding is suppressed, and the capture of the conductive particles between the opposing electrodes is improved, and as a result, an increase in the connection resistance is suppressed.
[0012] The circuit connecting adhesive on the above side may be any of the circuit connecting adhesives described in the following [2] to [4].
[0013] [2] The adhesive for circuit connection according to [1], wherein the thermal cationic polymerization initiator contains, as the onium salt, at least one compound selected from the group consisting of sulfonium salts and ammonium salts.
[0014] [3] The circuit connection adhesive according to [1] or [2], which is in the form of a film.
[0015] [4] An adhesive for circuit connection as described in [3], comprising a first adhesive layer and a second adhesive layer laminated on the first adhesive layer, the first adhesive layer containing the cationic polymerizable compound, the thermal cationic polymerization initiator, and the conductive particles.
[0016] Another aspect of the present invention relates to a connection structure as described in [5] below.
[0017] [5] A connection structure comprising: a first circuit member having a first electrode; a second circuit member having a second electrode; and a circuit connection portion disposed between the first circuit member and the second circuit member and electrically connecting the first electrode and the second electrode to each other, wherein the circuit connection portion comprises a cured product of the adhesive for circuit connection according to any one of [1] to [4].
[0018] Another aspect of the present invention relates to a method for producing a connection structure as described in [6] below.
[0019] [6] A method for manufacturing a connection structure, comprising the steps of: interposing a circuit connection adhesive according to any one of [1] to [4] between a first circuit member having a first electrode and a second circuit member having a second electrode; and thermocompression bonding the first circuit member and the second circuit member to electrically connect the first electrode and the second electrode to each other. Effect of the Invention
[0020] According to the present invention, it is possible to provide an adhesive for circuit connection, which is capable of obtaining a connection structure having sufficiently low connection resistance between opposing electrodes by thermocompression bonding at low temperature in a short time. [Brief description of the drawings]
[0021] [Figure 1] FIG. 1 is a schematic cross-sectional view showing one embodiment of the circuit connecting adhesive. [Diagram 2] FIG. 2 is a schematic cross-sectional view showing one embodiment of a connection structure. [Diagram 3] FIG. 3 is a schematic cross-sectional view showing a method for manufacturing the connection structure of FIG. [Figure 4] FIG. 4 is a diagram showing DSC curves of Experimental Example 1 and Experimental Example 2. [Diagram 5] FIG. 5 is a diagram showing DSC curves of Experimental Examples 3 and 4. [Figure 6] FIG. 6 is a diagram showing DSC curves of Experimental Examples 5 and 6. [Figure 7] FIG. 7 is a diagram showing DMA curves of Experimental Examples 3 and 4. [Figure 8] FIG. 8 is a diagram showing TG / DTA curves of Experimental Examples 3 and 4. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0022] In this specification, "(meth)acrylate" means at least one of acrylate and the corresponding methacrylate. The same applies to other similar expressions such as "(meth)acryl" and "(meth)acryloyl". Furthermore, "A or B" may include either A or B, or may include both. Furthermore, "room temperature" means 25°C.
[0023] Unless otherwise specified, the materials exemplified below may be used alone or in combination of two or more. When a plurality of substances corresponding to each component are present in the composition, the content of each component in the composition means the total amount of the plurality of substances present in the composition, unless otherwise specified. In addition, a numerical range indicated using "~" indicates a range including the numerical values described before and after "~" as the minimum and maximum values, respectively. In the numerical ranges described in stages in this specification, the upper limit or lower limit of a certain numerical range may be replaced by the upper limit or lower limit of a numerical range of another stage. In addition, in the numerical ranges described in this specification, the upper limit or lower limit of the numerical range may be replaced by the value shown in the examples. In addition, the upper limit and lower limit values described individually can be arbitrarily combined.
[0024] Hereinafter, embodiments of the present invention will be described, but the present invention is not limited to these embodiments.
[0025] <Circuit connection adhesive> The circuit connecting adhesive contains a cationic polymerizable compound (hereinafter also referred to as "component (a)"), a thermal cationic polymerization initiator (hereinafter also referred to as "component (b)"), and conductive particles (hereinafter also referred to as "component (c)"). In this circuit connecting adhesive, the cationic polymerizable compound contains an alicyclic epoxy compound, and the thermal cationic polymerization initiator contains an onium salt having an anion represented by the following formula (1) (tetrakis[3,5-bis(trifluoromethyl)phenyl]borate anion) (hereinafter also referred to as "onium salt (1)"). [ka]
[0026] The above-mentioned circuit connection adhesive is used, for example, to be interposed between a first circuit member having a first electrode and a second circuit member having a second electrode, and to thermally press the first circuit member and the second circuit member together, thereby electrically connecting the first electrode and the second electrode to each other.
[0027] The above circuit connection adhesive can provide a connection structure with sufficiently low connection resistance between opposing electrodes when thermocompression bonding during circuit connection is performed at low temperature for a short time. The above circuit connection adhesive also tends to provide a circuit connection structure with excellent connection reliability. That is, the connection structure obtained using the above circuit connection adhesive is unlikely to suffer from problems such as peeling even when exposed to a high-temperature, high-humidity atmosphere (e.g., 85°C, 85% RH) for a long period of time, and tends to be able to maintain a sufficiently low connection resistance.
[0028] The circuit connecting adhesive is, for example, in the form of a film. In the following, the circuit connecting adhesive will be described in detail using a film-like circuit connecting adhesive (circuit connecting adhesive film) as an example.
[0029] The adhesive film for circuit connection is an anisotropically conductive adhesive film consisting of an adhesive component containing a cationic polymerizable compound and a thermal cationic polymerization initiator, and conductive particles dispersed in the adhesive component. In this specification, the components other than the conductive particles contained in the adhesive film for circuit connection are collectively referred to as the adhesive component. In addition, "anisotropically conductive" means that the film is conductive in the direction of pressure and is insulating in the direction of no pressure.
[0030] [(a) Cationic polymerizable compound] The component (a) is, for example, a compound that is polymerized by a cationic species generated by a thermal cationic polymerization initiator (thermal cationic generator) by heat. The component (a) includes at least an alicyclic epoxy compound. Here, the alicyclic epoxy compound refers to a compound having an alicyclic epoxy group.
[0031] The number of alicyclic epoxy groups in one molecule of the alicyclic epoxy compound may be one or more than two. When the number of alicyclic epoxy groups in one molecule of the alicyclic epoxy compound is two or more, the crosslink density after curing tends to be high. The number of alicyclic epoxy groups in one molecule of the alicyclic epoxy compound may be, for example, 6 or less.
[0032] Examples of the alicyclic epoxy compounds include compounds obtained by oxidizing a compound having an alicyclic structure such as cyclohexene or cyclopentene (for example, a compound having cyclohexene oxide, cyclopentene oxide, or the like).
[0033] Specific examples of alicyclic epoxy compounds include 2-(3,4-epoxycyclohexyl-5,5-spiro-3,4-epoxy)cyclohexane-metadioxane, 3,4-epoxy-1-methylcyclohexyl-3,4-epoxy-1-methylhexanecarboxylate, 3,4-epoxy-3-methylcyclohexylmethyl-3,4-epoxy-3-methylcyclohexanecarboxylate, 3,4-epoxy-5-methylcyclohexylmethyl-3,4-epoxy-5-methylcyclohexanecarboxylate, 3,4-epoxy-6-methylcyclohexylcarboxylate, and 3,4-epoxycyclohexylmethyl. -3,4-epoxycyclohexane carboxylate, 6-methyl-3,4-epoxycyclohexylmethyl-6-methyl-3,4-epoxycyclohexane carboxylate, ethylene bis(3,4-epoxycyclohexane carboxylate), dicyclopentadiene diepoxide, bis(3,4-epoxycyclohexylmethyl)adipate, methylene bis(3,4-epoxycyclohexane), 3,4-epoxycyclohexylmethyl (meth)acrylate, (3,3',4,4'-diepoxy)bicyclohexyl, hydrogenated bisphenol A type epoxy resin, hydrogenated bisphenol F type epoxy resin, etc.
[0034] Commercially available alicyclic epoxy compounds include, for example, EHPE3150, EHPE3150CE, CEL (Celloxide) 8010, CEL (Celloxide) 2021P, and CEL (Celloxide) 2081 (trade names, manufactured by Daicel Corporation).
[0035] The alicyclic epoxy compounds may be used alone or in combination of two or more.
[0036] The epoxy equivalent of the alicyclic epoxy compound may be, for example, 100 to 300 g / eq from the viewpoint of adhesive strength. The epoxy equivalent is determined in accordance with JIS K 7236.
[0037] The content of the alicyclic epoxy compound may be 10% by mass or more, 15% by mass or more, or 20% by mass or more based on the total amount of the adhesive components, from the viewpoint of ensuring the curability of the circuit connecting adhesive. The content of the alicyclic epoxy compound may be 60% by mass or less, 55% by mass or less, or 50% by mass or less based on the total amount of the adhesive components, from the viewpoint of ensuring the film formability of the circuit connecting adhesive. From these viewpoints, the content of the alicyclic epoxy compound may be 10 to 60% by mass, 15 to 55% by mass, or 20 to 50% by mass, based on the total amount of the adhesive components.
[0038] The (a) component may further contain a cationic polymerizable compound other than the alicyclic epoxy compound. Examples of the cationic polymerizable compound other than the alicyclic epoxy compound include epoxy compounds other than the alicyclic epoxy compound and compounds having a cyclic ether group such as oxetane compounds. Among these, when the (a) component further contains an oxetane compound, the crosslink density is increased, and the effect of reducing the connection resistance tends to be more remarkable, and more excellent connection reliability tends to be obtained.
[0039] The oxetane compound is a compound having an oxetanyl group. The number of oxetanyl groups in one molecule of the oxetane compound may be one or more than two. When the number of oxetanyl groups in one molecule of the oxetane compound is two or more, the crosslink density after curing tends to be higher, and a synergistic effect is easily obtained by combining with an alicyclic epoxy compound. The number of oxetanyl groups in one molecule of the oxetane compound may be, for example, six or less.
[0040] Examples of the oxetane compound include 2-ethylhexyl oxetane, 3-hydroxymethyl-3-methyl oxetane, 3-hydroxymethyl-3-ethyl oxetane, 3-hydroxymethyl-3-propyl oxetane, 3-hydroxymethyl-3-normal butyl oxetane, 3-hydroxymethyl-3-phenyl oxetane, 3-hydroxymethyl-3-benzyl oxetane, 3-hydroxyethyl-3-methyl oxetane, 3-hydroxyethyl-3-ethyl oxetane, 3-hydroxyethyl-3-propyl oxetane, 3-hydroxyethyl-3-phenyl oxetane, 3-hydroxypropyl-3-methyl oxetane, 3-hydroxypropyl-3-ethyl oxetane, 3-hydroxypropyl-3-propyl oxetane, 3-hydroxypropyl-3-phenyl oxetane, 3-hydroxybutyl-3-methyl oxetane, and 4,4'-bis[(3-ethyl-3-oxetanyl)methoxymethyl]biphenyl.
[0041] Commercially available oxetane compounds include, for example, ETERNACOLL OXBP (trade name, 4,4'-bis[(3-ethyl-3-oxetanyl)methoxymethyl]biphenyl, manufactured by Ube Industries, Ltd.), OXSQ, OXT-121, OXT-221, OXT-101, and OXT-212 (trade names, manufactured by Toagosei Co., Ltd.).
[0042] The oxetane compounds may be used alone or in combination of two or more.
[0043] When component (a) further contains an oxetane compound, the mass ratio of the content of the oxetane compound to the content of the alicyclic epoxy compound (content of oxetane compound / content of alicyclic epoxy compound) may be 0.2 or more, 0.5 or more, 1.0 or more, or 1.5 or more, and may be 5.0 or less, 4.0 or less, 3.0 or less, or 2.5 or less, or may be 0.2 to 5.0, 0.5 to 4.0, 1.0 to 3.0, or 1.5 to 2.5, from the viewpoint of improving the reactivity of the oxetane compound and making it easier to obtain a synergistic effect by combining it with the alicyclic epoxy compound.
[0044] The content of component (a) may be 10 mass% or more, 15 mass% or more, or 20 mass% or more based on the total amount of the adhesive components, from the viewpoint of ensuring the curability of the circuit connecting adhesive. The content of component (a) may be 50 mass% or less, 40 mass% or less, or 30 mass% or less based on the total amount of the adhesive components, from the viewpoint of ensuring the film formability of the circuit connecting adhesive. From these viewpoints, the content of component (a) may be 10 to 50 mass%, 15 to 40 mass%, or 20 to 30 mass% based on the total amount of the adhesive components.
[0045] [(b) Thermal cationic polymerization initiator] The component (b) is a compound that generates a cationic species (such as an acid) upon heating to initiate polymerization, and is, for example, a salt compound composed of a cation and an anion. The component (b) contains at least an onium salt (1).
[0046] The cation of the onium salt (1) is not particularly limited. The onium salt (1) may be, for example, a sulfonium salt, a phosphonium salt, an ammonium salt, a diazonium salt, or an iodonium salt. Among these, when at least one selected from the group consisting of a sulfonium salt and an ammonium salt is used, a lower connection resistance tends to be obtained. This tendency becomes stronger when an ammonium salt (particularly anilinium salt) is used.
[0047] Examples of anilinium salts include N-alkylanilinium salts, N,N-dialkylanilinium salts, N,N,N-trialkylanilinium salts, N-benzylanilinium salts (including N-alkyl-N-benzylanilinium salts and N,N-dialkyl-N-benzylanilinium salts), etc. In these anilinium salts, the hydrocarbon group (alkyl and benzyl) bonded to the nitrogen atom may have a substituent.
[0048] From the viewpoint of improving the effect of reducing connection resistance during thermocompression bonding at low temperature in a short time, the onium salt (1) may be a salt having a cation (N-benzylanilinium ion) represented by the following formula (2). [ka]
[0049] In formula (2), R 1 , R 2 , R 3 , R 8 , R 9 and R 10 each independently represents a hydrogen atom, a halogen atom, an alkyl group having 1 to 3 carbon atoms, an alkoxy group having 1 to 12 carbon atoms, a nitro group, an amino group, an alkylamino group, a cyano group, an alkoxycarbonyl group, or a carbonyl group; R 4 and R 5 each independently represents a hydrogen atom, an alkyl group having 1 to 3 carbon atoms, or a halogen atom; R 6 and R 7 each independently represents a halogen atom or an alkyl group having 1 to 3 carbon atoms.
[0050] Specific examples of the cation represented by the above formula (2) include N-benzyl-N,N-dimethylanilinium ion, N-(4-nitrobenzyl)-N,N-dimethylanilinium ion, N-(4-methoxybenzyl)-N,N-dimethylanilinium ion, N-(α-phenylbenzyl)-N,N-dimethylanilinium ion, N-(α-methylbenzyl)-N,N-dimethylanilinium ion, N-(1-naphthylmethyl)-N,N-dimethylanilinium ion, and N-cinnamyl-N,N-dimethylanilinium ion.
[0051] The onium salt (1) can be prepared, for example, by preparing a salt of the anion represented by the above formula (1) and a sodium ion, and a salt of an ion that serves as a counter cation of the onium salt (1) and an iodide ion, and mixing them.
[0052] The onium salt (1) may be used alone or in combination of two or more kinds.
[0053] The content of the onium chloride (1) may be 10 parts by mass or more, 15 parts by mass or more, or 20 parts by mass or more, relative to 100 parts by mass of the alicyclic epoxy compound, from the viewpoint of improving the effect of reducing the connection resistance during thermocompression bonding at low temperature in a short time. The content of the onium chloride (1) may be 45 parts by mass or less, 40 parts by mass or less, or 35 parts by mass or less, relative to 100 parts by mass of the alicyclic epoxy compound, from the viewpoint of improving the effect of reducing the connection resistance during thermocompression bonding at low temperature in a short time. From these viewpoints, the content of the onium chloride (1) may be 10 to 45 parts by mass, 10 to 40 parts by mass, 15 to 45 parts by mass, 15 to 40 parts by mass, or 20 to 35 parts by mass, relative to 100 parts by mass of the alicyclic epoxy compound.
[0054] The content of the onium chloride (1) may be 0.5 mass% or more, 1.0 mass% or more, or 3.0 mass% or more based on the total amount of the adhesive components, from the viewpoint of improving the effect of reducing the connection resistance during thermocompression bonding at low temperature in a short time. The content of the onium chloride (1) may be 20 mass% or less, 15 mass% or less, or 10 mass% or less based on the total amount of the adhesive components, from the viewpoint of improving the effect of reducing the connection resistance during thermocompression bonding at low temperature in a short time. From these viewpoints, the content of the onium chloride (1) may be 0.5 to 20 mass%, 1.0 to 15 mass%, or 3.0 to 10 mass% based on the total amount of the adhesive components.
[0055] The component (b) may contain a thermal cationic polymerization initiator other than the onium chloride (1). The content of the onium chloride (1) based on the total mass of the component (b) may be, for example, 90 mass% or more, or may be 100 mass%.
[0056] The content of the (b) component may be 0.5 mass% or more, 1.0 mass% or more, or 3.0 mass% or more based on the total amount of the adhesive components, from the viewpoint of improving the effect of reducing the connection resistance during thermocompression bonding at low temperature in a short time. The content of the (b) component may be 20 mass% or less, 15 mass% or less, or 10 mass% or less based on the total amount of the adhesive components, from the viewpoint of improving the effect of reducing the connection resistance during thermocompression bonding at low temperature in a short time. From these viewpoints, the content of the (b) component may be 0.5 to 20 mass%, 1.0 to 15 mass%, or 3.0 to 10 mass% based on the total amount of the adhesive components.
[0057] [(c) Conductive particles] The component (c) is not particularly limited as long as it is a particle having electrical conductivity, and may be a metal particle made of a metal such as gold, silver, palladium, nickel, copper, or solder, or a conductive carbon particle made of conductive carbon. The component (c) may be a coated conductive particle having a core containing non-conductive glass, ceramic, plastic (polystyrene, etc.), and a coating layer containing the above metal or conductive carbon and coating the core. Among these, when the component (c) contains at least one selected from the group consisting of metal particles and coated conductive particles formed of a heat-fusible metal (particularly when the coated conductive particles are included), it becomes easy to deform by heating and / or pressing, and when the electrodes are electrically connected to each other, the contact area between the electrodes and the conductive particles can be increased, and the conductivity between the electrodes can be further improved.
[0058] The average particle diameter of the component (c) may be 1.0 μm or more, 2.0 μm or more, or 2.5 μm or more from the viewpoint of excellent dispersibility and conductivity. The average particle diameter of the component (c) may be 6.0 μm or less, 5.5 μm or less, or 5.0 μm or less from the viewpoint of ensuring insulation between adjacent electrodes. From these viewpoints, the average particle diameter of the component (c) may be 1.0 to 6.0 μm, 2.0 to 5.5 μm, or 2.5 to 5.0 μm. The particle diameters of 300 conductive particles contained in the circuit connecting adhesive are measured by observation using a scanning electron microscope (SEM), and the average value of the particle diameters obtained is defined as the average particle diameter of the component (c). When the conductive particles are not spherical, the particle diameter of the conductive particles is defined as the diameter of a circle circumscribing the conductive particles in an image observed by SEM.
[0059] The component (c) may be uniformly dispersed in the adhesive film for circuit connection. From the viewpoint of obtaining a stable connection resistance, the particle density of the component (c) in the adhesive film for circuit connection is 100 particles / mm 2 More than 1000 pieces / mm 2 or more than 3000 pieces / mm 2 From the viewpoint of ensuring the insulation between adjacent electrodes, the particle density of the component (c) in the adhesive film for circuit connection may be 100,000 particles / mm 2 Below, 50000 pieces / mm 2 Less than or equal to 30,000 pieces / mm 2 From these viewpoints, the particle density of the component (c) in the adhesive film for circuit connection may be 100 to 100,000 particles / mm 2 , 1000~50000 pieces / mm 2 Or 3000~30000 pieces / mm 2 It may be.
[0060] The content of component (c) may be 10 mass % or more, 20 mass % or more, or 30 mass % or more, based on the total mass of the adhesive for circuit connection, from the viewpoint of obtaining a stable connection resistance, and the content of component (c) may be 60 mass % or less, 50 mass % or less, or 40 mass % or less, based on the total mass of the adhesive for circuit connection, from the viewpoint of ensuring insulation between adjacent electrodes.
[0061] [Other ingredients] The adhesive film for circuit connection may further contain components (other components) other than the above-mentioned components. Examples of the other components include thermoplastic resins, coupling agents, fillers, etc. These components are included in the adhesive component.
[0062] -Thermoplastic resin The thermoplastic resin contributes to improving the film-forming properties of the circuit-connecting adhesive. Examples of the thermoplastic resin include phenoxy resin, polyester resin, polyamide resin, polyurethane resin, polyester urethane resin, acrylic rubber, epoxy resin (solid at 25°C), etc. These may be used alone or in combination of two or more.
[0063] The weight average molecular weight (Mw) of the thermoplastic resin may be, for example, 5,000 to 200,000, 10,000 to 100,000, 20,000 to 80,000, or 40,000 to 60,000. The weight average molecular weight of the thermoplastic resin refers to a value measured by gel permeation chromatography (GPC) and converted using a calibration curve of standard polystyrene.
[0064] The content of the thermoplastic resin may be 1.0 mass% or more, 5.0 mass% or more, 10 mass% or more, or 15 mass% or more, based on the total amount of the adhesive components. The content of the thermoplastic resin may be 50 mass% or less, 40 mass% or less, 30 mass% or less, or 20 mass% or less, based on the total amount of the adhesive components. The content of the thermoplastic resin may be 1.0 to 50 mass%, 5.0 to 40 mass%, 10 to 30 mass%, or 15 to 20 mass%, based on the total amount of the adhesive components.
[0065] -Coupling Agent The coupling agent contributes to improving the adhesiveness. The coupling agent may be, for example, a silane coupling agent. Examples of the coupling agent include vinyl trimethoxysilane, vinyl triethoxysilane, 3-glycidoxypropyl trimethoxysilane, 3-glycidoxypropyl methyl diethoxysilane, 3-(meth)acryloxypropyl methyl dimethoxysilane, 3-(meth)acryloxypropyl trimethoxysilane, 3-(meth)acryloxypropyl methyl diethoxysilane, 3-(meth)acryloxypropyl triethoxysilane, N-2-(aminoethyl)-3-aminopropyl methyl dimethoxysilane, N-phenyl-3-aminopropyl trimethoxysilane, 3-ureidopropyl triethoxysilane, 3-mercaptopropyl trimethoxysilane, 3-isocyanate propyl triethoxysilane, and condensates thereof. These may be used alone or in combination of two or more.
[0066] The content of the coupling agent may be 0.1% by mass or more, 0.5% by mass or more, 1.0% by mass or more, or 1.5% by mass or more, based on the total amount of the adhesive components. The content of the coupling agent may be 10% by mass or less, 8.0% by mass or less, 5.0% by mass or less, or 3.0% by mass or less, based on the total amount of the adhesive components. The content of the coupling agent may be 0.1 to 10% by mass, 0.5 to 8.0% by mass, 1.0 to 5.0% by mass, or 1.5 to 3.0% by mass, based on the total amount of the adhesive components.
[0067] -Filling material The filler contributes to improving connection reliability. Examples of the filler include non-conductive fillers (e.g., non-conductive particles). The filler may be either an inorganic filler or an organic filler.
[0068] Examples of the inorganic filler include metal oxide particles such as silica particles, alumina particles, silica-alumina particles, titania particles, and zirconia particles; metal nitride particles, etc. These may be used alone or in combination of two or more.
[0069] Examples of the organic filler include silicone particles, methacrylate-butadiene-styrene particles, acrylic-silicone particles, polyamide particles, polyimide particles, etc. These may be used alone or in combination of two or more.
[0070] The filler may be an inorganic filler from the viewpoint of improving the film formability and the reliability of the connection structure. This effect tends to be significantly obtained when the filler contains silica particles. The silica particles may be crystalline silica particles or non-crystalline silica particles. These silica particles may be synthetic products. The method for synthesizing the silica particles may be a dry method or a wet method. The silica particles may contain at least one type selected from the group consisting of fumed silica particles and sol-gel silica particles.
[0071] The silica particles may be surface-treated silica particles from the viewpoint of excellent dispersibility in the adhesive component.The surface-treated silica particles may be, for example, silica particles surface-treated with a silane compound such as an alkoxysilane compound, a disilazane compound, or a siloxane compound, or may be silica particles surface-treated with a silane coupling agent.The surface-treated silica particles are, for example, silica particles whose surface hydroxyl groups are hydrophobized with a silane compound or a silane coupling agent.
[0072] Examples of the alkoxysilane compound include methyltrimethoxysilane, dimethyldimethoxysilane, phenyltrimethoxysilane, dimethoxydiphenylsilane, tetraethoxysilane, methyltriethoxysilane, dimethyldiethoxysilane, phenyltriethoxysilane, n-propyltrimethoxysilane, n-propyltriethoxysilane, hexyltrimethoxysilane, hexyltriethoxysilane, octyltriethoxysilane, decyltrimethoxysilane, 1,6-bis(trimethoxysilyl)hexane, and 3,3,3-trifluoropropyltrimethoxysilane.
[0073] Examples of the disilazane compound include 1,1,1,3,3,3-hexamethyldisilazane, 1,3-diphenyltetramethyldisilazane, 1,3-bis(3,3,3-trifluoropropyl)-1,1,3,3-tetramethyldisilazane, and 1,3-divinyl-1,1,3,3-tetramethyldisilazane.
[0074] Examples of the siloxane compound include tetradecamethylcycloheptasiloxane, decamethylcyclopentasiloxane, hexaphenylcyclosiloxane, octadecamethylcyclononasiloxane, hexadecamethylcyclooctasiloxane, dodecamethylcyclohexasiloxane, octaphenylcyclotetrasiloxane, hexamethylcyclotrisiloxane, heptaphenyldisiloxane, tetradecamethylhexasiloxane, dodecamethylpentasiloxane, hexamethylcyclohex ... Tyldisiloxane, decamethyltetrasiloxane, hexamethoxydisiloxane, octamethyltrisiloxane, octamethylcyclotetrasiloxane, 1,3-vinyltetramethyldisiloxane, 2,4,6-trimethyl-2,4,6-trivinylcyclotrisiloxane, 1,3-dimethoxy-1,1,3,3-tetraphenyldisiloxane, 1,1,3,3-tetramethyl-1,3-diphenyldisiloxane, 1,3-dimethyl-1,3-diphenyl-1,3- Divinyldisiloxane, 2,4,6,8-tetramethyl-2,4,6,8-tetravinylcyclotetrasiloxane, 1,1,1,3,5,5,5,-heptamethyl-3-(3-glycidyloxypropyl)trisiloxane, 1,3,5-tris(3,3,3-trifluoropropyl)-1,3,5-trimethylcyclotrisiloxane, 1,1,1,3,5,5,5,-heptamethyl-3-[(trimethylsilyl)oxy]trisiloxane, 1,3,-bis[2-(7 -oxabicyclo[4.1.0]heptan-3-yl)ethyl]-1,1,3,3,-tetramethyldisiloxane, 1,1,1,5,5,5-hexamethyl-3-[(trimethylsilyl)oxy]-3-vinyltrisiloxane, 3-[[dimethyl(vinyl)silyl]oxy]-1,1,5,5,-tetramethyl-3-phenyl-1,5-vinyltrisiloxane, octavinyloctasilsesquioxane, and octaphenyloctasilasilsesquioxane.
[0075] Silane coupling agents include vinyltrimethoxysilane, vinyltriethoxysilane, 2-(3,4-epoxycyclohexyl)ethyltrimethoxysilane, 3-glycidoxypropylmethyldimethoxysilane, 3-glycidoxypropyltrimethoxysilane, 3-glycidoxypropylmethyldiethoxysilane, 3-glycidoxypropyltriethoxysilane, p-styryltrimethoxysilane, 3-methacryloxypropylmethyldimethoxysilane, 3-methacryloxypropyltrimethoxysilane, 3-methacryloxypropylmethyldiethoxysilane, 3-methacryloxypropyltriethoxysilane, 3-acryloxypropyltrimethoxysilane, N-2-(amino) Noethyl)-3-aminopropylmethyldimethoxysilane, N-2-(aminoethyl)-3-aminopropyltrimethoxysilane, 3-aminopropyltrimethoxysilane, 3-aminopropyltriethoxysilane, 3-triethoxysilyl-N-(1,3-dimethyl-butylidene)propylamine, N-phenyl-3-aminopropyltrimethoxysilane, tris-(trimethoxysilylpropyl)isocyanurate, 3-ureidopropyltrialkoxysilane, 3-mercaptopropylmethyldimethoxysilane, 3-mercaptopropyltrimethoxysilane, 3-isocyanatopropyltriethoxysilane, 3-trimethoxysilylpropylsuccinic anhydride, and the like.
[0076] The silica particles that have been surface-treated with a silane compound or a silane coupling agent may be further surface-treated with a silane compound such as 3-methacryloxypropyltrimethoxysilane, vinyltrimethoxysilane, or trimethoxyphenylsilane to further hydrophobize the hydroxyl group residues on the surface of the silica particles.
[0077] From the viewpoint of easily controlling the fluidity when the circuit connection adhesive film is pressed, and from the viewpoint of improving the mechanical properties and water resistance of the connection structure after pressing, the surface-treated silica particles may contain at least one selected from the group consisting of a reaction product (hydrolysis product) of silica and trimethoxyoctylsilane, a reaction product of silica and dimethylsiloxane, a reaction product of silicon dioxide or silica and dichloro(dimethyl)silane, a reaction product (hydrolysis product) of silica and bis(trimethylsilyl)amine, and a reaction product of silica and hexamethyldisilazane. Among these, it is preferable to contain at least one selected from the group consisting of a reaction product of silica and trimethoxyoctylsilane, and a reaction product of silica and bis(trimethylsilyl)amine.
[0078] The content of the filler may be 0.1% by mass or more, 1.0% by mass or more, 5.0% by mass or more, or 10% by mass or more, based on the total amount of the adhesive components. The content of the filler may be 50% by mass or less, 40% by mass or less, 30% by mass or less, or 20% by mass or less, based on the total amount of the adhesive components. The content of the filler may be 0.1 to 50% by mass, 1.0 to 40% by mass, 5.0 to 30% by mass, or 10 to 20% by mass, based on the total amount of the adhesive components.
[0079] The adhesive film for circuit connection may be in an uncured state or in a partially cured state.
[0080] The thickness of the adhesive film for circuit connection may be, for example, 5 μm or more, or 10 μm or more, and may be 30 μm or less, or 20 μm or less.
[0081] The adhesive film for circuit connection may have a single layer structure or a multilayer structure (a structure of two or more layers). An example of an adhesive film for circuit connection having a multilayer structure is shown in FIG.
[0082] Fig. 1 is a schematic cross-sectional view of an adhesive film for circuit connection having a two-layer structure. The adhesive film for circuit connection 1 shown in Fig. 1 comprises a first adhesive layer 1A and a second adhesive layer 1B. The first adhesive layer 1A is made of a first adhesive component 2A and conductive particles 3A dispersed in the first adhesive component 2A. The second adhesive layer 1B is made of a second adhesive component 2B.
[0083] At least one of the first adhesive component 2A and the second adhesive component 2B contains an alicyclic epoxy compound and an onium salt (1). The contents of the alicyclic epoxy compound and the onium salt (1) in the first adhesive component 2A and the second adhesive component 2B (based on the total amount of the first adhesive component 2A and the total amount of the second adhesive component) may be in the same range as the contents of these components in the entire adhesive film for circuit connection described above (based on the total amount of the adhesive components). In addition, the contents of the (a) component, the (b) component, and other components in the first adhesive component 2A and the second adhesive component 2B (based on the total amount of the first adhesive component 2A and the total amount of the second adhesive component) may also be in the same range as the contents of these components in the entire adhesive film for circuit connection described above (based on the total amount of the adhesive components).
[0084] The content of the conductive particles 3A in the first adhesive layer 1A may be 10 mass % or more, 20 mass % or more, or 30 mass % or more based on the total mass of the first adhesive layer 1A from the viewpoint of obtaining a stable connection resistance. The content of the conductive particles 3A in the first adhesive layer 1A may be 60 mass % or less, 50 mass % or less, or 40 mass % or less based on the total mass of the first adhesive layer 1A from the viewpoint of ensuring insulation between adjacent electrodes.
[0085] The content of the conductive particles in the second adhesive layer 1B is, for example, 1 mass % or less, and may be 0 mass %, based on the total mass of the second adhesive layer. In other words, the second adhesive layer 1B does not need to contain conductive particles.
[0086] The first adhesive layer 1A and the second adhesive layer 1B may each be in an uncured state or in a partially cured state.
[0087] The thickness of the first adhesive layer 1A may be, for example, 3 μm or more, or 5 μm or more, and may be 15 μm or less, or 10 μm or less.
[0088] The thickness of the second adhesive layer 1B may be, for example, 5 μm or more, or 10 μm or more, and may be 20 μm or less, or 15 μm or less.
[0089] The ratio of the thickness of the first adhesive layer 1A to the thickness of the second adhesive layer 1B (thickness of the first adhesive layer 1A / thickness of the second adhesive layer 1B) may be 0.1 or more, or 0.3 or more, and may be 1.0 or less, or 0.5 or less.
[0090] The adhesive film for circuit connection can be produced, for example, by dissolving or dispersing the above-mentioned components (a), (b), and (c), and, if necessary, other components, in an organic solvent by stirring, mixing, kneading, etc., to prepare a varnish composition (varnish-like adhesive composition), applying the varnish composition to a release-treated substrate using a knife coater, roll coater, applicator, comma coater, die coater, etc., and then volatilizing the organic solvent by heating. At this time, the thickness of the adhesive film for circuit connection can be adjusted by adjusting the amount of the varnish composition applied.
[0091] The organic solvent used in the preparation of the varnish composition is not particularly limited as long as it has the property of dissolving or dispersing each component uniformly. Examples of such organic solvents include toluene, acetone, methyl ethyl ketone, methyl isobutyl ketone, ethyl acetate, propyl acetate, butyl acetate, etc. These organic solvents can be used alone or in combination of two or more. The stirring and mixing or kneading in the preparation of the varnish composition can be performed using, for example, a stirrer, a grinding machine, a three-roll mill, a ball mill, a bead mill, a homodisper, etc.
[0092] The substrate is not particularly limited as long as it has heat resistance that can withstand the heating conditions when volatilizing the organic solvent. Examples of such substrates include substrates (e.g., films) made of oriented polypropylene (OPP), polyethylene terephthalate (PET), polyethylene naphthalate, polyethylene isophthalate, polybutylene terephthalate, polyolefin, polyacetate, polycarbonate, polyphenylene sulfide, polyamide, polyimide, cellulose, ethylene-vinyl acetate copolymer, polyvinyl chloride, polyvinylidene chloride, synthetic rubber, liquid crystal polymer, and the like.
[0093] The heating conditions for volatilizing the organic solvent from the varnish composition applied to the substrate can be appropriately set according to the organic solvent used, etc. The heating conditions may be, for example, at 40 to 120° C. for 0.1 to 10 minutes.
[0094] A portion of the solvent may remain unremoved in the adhesive film for circuit connection. The content of the solvent in the adhesive film for circuit connection may be, for example, 10 mass % or less based on the total mass of the adhesive film.
[0095] When the adhesive film for circuit connection is a two-layer adhesive film as shown in Fig. 1, the adhesive film may be produced by forming a second adhesive layer on a substrate in the same manner as above, and then forming a first adhesive layer on the second adhesive layer in the same manner. Alternatively, a first adhesive film having a first adhesive layer on a substrate and a second adhesive film having a second adhesive layer on a substrate may be produced, and then the adhesive film may be produced by laminating them together.
[0096] The above-described adhesive film for circuit connection may be provided in a state in which it is peelably attached to a substrate (for example, the substrate used in the above-mentioned production). In other words, in one aspect, the present invention provides a substrate-attached adhesive film comprising a substrate and an adhesive film for circuit connection formed on the substrate.
[0097] <Connection structure and method for producing same> Another embodiment of the present invention is a connection structure comprising a first circuit member having a first electrode, a second circuit member having a second electrode, and a circuit connection portion disposed between the first circuit member and the second circuit member and electrically connecting the first electrode and the second electrode to each other, wherein the circuit connection portion includes a cured product of the circuit connection adhesive.
[0098] Another embodiment of the present invention is a method for manufacturing a connection structure, comprising the steps of interposing the circuit connection adhesive between a first circuit member having a first electrode and a second circuit member having a second electrode, and thermocompressing the first circuit member and the second circuit member to electrically connect the first electrode and the second electrode to each other.
[0099] Hereinafter, a connection structure using the above-mentioned adhesive film 1 for circuit connection as a circuit connecting material and a method for producing the same will be described.
[0100] Fig. 2 is a schematic cross-sectional view showing one embodiment of a connection structure. As shown in Fig. 2, a connection structure 10 includes a first circuit member 4 and a second circuit member 5 facing each other, and a circuit connection portion 6 that connects the first circuit member 4 and the second circuit member 5 between the first circuit member 4 and the second circuit member 5.
[0101] The first circuit member 4 includes a first circuit board 41 and a first electrode 42 formed on a main surface 41a of the first circuit board 41. The second circuit member 5 includes a second circuit board 51 and a second electrode 52 formed on a main surface 51a of the second circuit board 51.
[0102] There is no particular limitation on the first circuit member 4 and the second circuit member 5 as long as they are members on which electrodes that require electrical connection are formed. Examples of members on which electrodes are formed (circuit members, etc.) include inorganic substrates such as semiconductors, glass, and ceramics; polyimide substrates such as TCP, FPC, and COF; substrates on which electrodes are formed on films such as polycarbonate, polyester, and polyethersulfone; and printed wiring boards, and a combination of two or more of these may be used.
[0103] The circuit connection portion 6 includes a cured product of the adhesive film for circuit connection 1. The circuit connection portion 6 has, for example, a first region 7 located on the first circuit member 4 side in the direction in which the first circuit member 4 and the second circuit member 5 face each other (hereinafter, "facing direction"), a second region 8 located on the second circuit member 5 side in the facing direction, and conductive particles 3A interposed at least between the first electrode 42 and the second electrode 52 (in contact with both the first electrode 42 and the second electrode 52) and electrically connecting the first electrode 42 and the second electrode 52 to each other. The conductive particles 3A may be disposed not only between the facing first electrode 42 and second electrode 52 but also between the main surface 41a of the first circuit board 41 and the main surface 51a of the second circuit board 51.
[0104] The first region 7 is made of, for example, an insulating material containing a cured product of the first adhesive component 2A. The second region 8 is made of, for example, an insulating material containing a cured product of the second adhesive component 2B. The circuit connection part 6 does not have to have two regions such as the first region 7 and the second region 8, and may be made of, for example, a cured product obtained by curing a mixture of the first adhesive component 2A and the second adhesive component 2B.
[0105] FIG. 3 is a schematic cross-sectional view showing a method for producing a connection structure 10. In the method for producing a connection structure 10, as shown in FIG. 3(a), first, a first circuit member 4 and an adhesive film 1 for circuit connection are prepared. Next, the adhesive film 1 for circuit connection is placed on the main surface 41a of the first circuit member 4. When the adhesive film 1 for circuit connection is laminated on a substrate (not shown), a laminate including the adhesive film 1 for circuit connection and the substrate is placed on the first circuit member 4 so that the adhesive film 1 side for circuit connection of the substrate faces the first circuit member 4. At this time, the number of conductive particles captured between the opposing electrodes can be increased by facing the first adhesive layer 1A side of the adhesive film 1 for circuit connection to the main surface 41a of the first circuit member 4.
[0106] Then, the adhesive film for circuit connection 1 is pressed in the directions of arrows A and B in Fig. 3(a) to temporarily connect the adhesive film for circuit connection 1 to the first circuit member 4 (see Fig. 3(b)). At this time, heating may be performed together with the pressing.
[0107] 3(c), a second circuit member 5 is further placed on the adhesive film 1 for circuit connection placed on the first circuit member 4 with the second electrode 52 facing the first circuit member 4 (i.e., the first electrode 42 and the second electrode 52 are placed opposite each other, and the adhesive film 1 for circuit connection is interposed between the first circuit member 4 and the second circuit member 5). If the adhesive film 1 for circuit connection is laminated on a substrate (not shown), the substrate is peeled off and then the second circuit member 5 is placed on the adhesive film 1 for circuit connection.
[0108] Then, the adhesive film 1 for circuit connection is thermocompressed in the directions of arrows A and B in Fig. 3(c). This causes the adhesive film 1 for circuit connection to harden, and completes the electrical connection between the first electrode 42 and the second electrode 52. As a result, a connection structure 10 as shown in Fig. 2 is obtained.
[0109] In the connection structure 10 obtained as described above, it is possible to bring the conductive particles 3 into contact with both the opposing first electrode 42 and second electrode 52, and it is possible to sufficiently reduce the connection resistance between the first electrode 42 and the second electrode 52. Therefore, it is possible to smooth the flow of current between the first electrode 42 and the second electrode 52, and it is possible to fully exert the functions of the first circuit member 4 and the second circuit member 5.
[0110] The temperature during thermocompression bonding is a temperature at which the adhesive film for circuit connection 1 can be sufficiently cured to bond the first circuit member 4 and the second circuit member 5. The temperature during thermocompression bonding may be less than 130°C, or may be 125°C or less or 115°C or less. The temperature during thermocompression bonding may be 110°C or more. Note that the above temperature is the maximum temperature that the adhesive film for circuit connection can reach.
[0111] The time for thermocompression bonding may be less than 10 seconds, or may be 7 seconds or less, or may be 5 seconds or less. The time for thermocompression bonding may be 3 seconds or more, or may be 4 seconds or more. EXAMPLES
[0112] The present invention will be specifically described below with reference to experimental examples, but the present invention is not limited to the following experimental examples.
[0113] In the experimental examples, the following materials were used. Thermal cationic polymerization initiator A1: (N,N-dimethyl,N-(4-methoxybenzyl)anilinium tetrakis[3,5-bis(trifluoromethyl)phenyl]borate) synthesized in Synthesis Example 1 below A2: N,N-dimethyl,N-(4-methoxybenzyl)anilinium tetrakis(pentafluorophenyl)borate synthesized in Synthesis Example 2 below Cationic polymerizable compounds B1: Bis-7-oxabicyclo[4,1,0]heptane (product name: Celloxide 8010, manufactured by Daicel Corporation) B2: 4,4'-bis[(3-ethyl-3-oxetanyl)methyl]biphenyl (trade name: OXBP, manufactured by Ube Industries, Ltd.) B3: Bisphenol A type epoxy resin (epoxy equivalent: 180 to 190, product name: YL980, manufactured by Mitsubishi Chemical Corporation) ·Thermoplastic resin C1: Bisphenol A and bisphenol F copolymer phenoxy resin (weight average molecular weight: 62,000, glass transition temperature: 71°C, product name: ZX-1356-2, manufactured by Nippon Steel Chemical & Material Co., Ltd.), diluted with organic solvent (2-butanone) to 50% non-volatile content by mass. C2: P-1 (fluorene-type phenoxy resin) synthesized in Synthesis Example 3 below C3: Bisphenol A type solid epoxy resin (product name: jER1010, manufactured by Mitsubishi Chemical Corporation) Conductive particles D1: Conductive particles prepared in Preparation Example 1 below Coupling Agent E1: γ-glycidoxypropyltrimethoxysilane (product name: KBM-403, manufactured by Shin-Etsu Chemical Co., Ltd.) ·Filling material F1: Surface-treated silica particles (hydrolysis product of silica and bis(trimethylsilyl)amine) F2: Surface-treated silica fine particles (hydrolysis product of trimethoxyoctylsilane and silica, trade name: Aerosil R805, manufactured by Evonik Industries AG, diluted with an organic solvent to a non-volatile content of 10% by mass)
[0114] <Synthesis Example 1> (Synthesis of N,N-dimethyl,N-(4-methoxybenzyl)anilinium tetrakis[3,5-bis(trifluoromethyl)phenyl]borate) [Process 1] A 200 ml Erlenmeyer flask with a magnetic stirrer and a stirrer tip was prepared, and 100 ml of dehydrated acetone (manufactured by FUJIFILM Wako Pure Chemical Industries, Ltd.), 3.11 g of 4-methoxybenzyl chloride (20 mmol, manufactured by FUJIFILM Wako Pure Chemical Industries, Ltd.), and 6.00 g of sodium iodide (40 mmol, manufactured by FUJIFILM Wako Pure Chemical Industries, Ltd.) were dissolved and stirred at room temperature for 2 hours. After filtering the precipitate after stirring, the solution was further washed three times with 100 ml of hexane (manufactured by FUJIFILM Wako Pure Chemical Industries, Ltd.) and 50 ml of water, and the organic layer was dried with 20 g of sodium sulfate (manufactured by FUJIFILM Wako Pure Chemical Industries, Ltd.). By distilling off the organic layer, 4.61 g (yield 99%) of 4-methoxybenzyl iodide was obtained as a pale yellow liquid.
[0115] [Process 2] A 200ml Erlenmeyer flask with a magnetic stirrer and a stirrer tip was prepared, and 100ml of hexane (FUJIFILM Wako Pure Chemical Industries, Ltd.) and 4.61g (19mmol, FUJIFILM Wako Pure Chemical Industries, Ltd.) of 4-methoxybenzyl iodide were mixed. 2.30g (19mmol, FUJIFILM Wako Pure Chemical Industries, Ltd.) of N,N-dimethylaniline mixed with 5ml of hexane was dropped into the Erlenmeyer flask and stirred at room temperature for 30 minutes. 50ml of methanol (FUJIFILM Wako Pure Chemical Industries, Ltd.) was added to the reaction mixture after stirring, and the methanol layer was washed three times with 100ml of hexane. After that, 6.00g (85% yield) of N,N-dimethyl,N-(4-methoxybenzyl)anilinium iodide was obtained by distilling off the methanol.
[0116] (Process 3A) A 200ml Erlenmeyer flask with a magnetic stirrer and a stirrer tip was prepared, and 50ml of ethyl acetate (Fujifilm Wako Pure Chemical Industries, Ltd.) and 50ml of water were mixed. 1.89g (5.1mmol) of N,N-dimethyl,N-(4-methoxybenzyl)anilinium iodide dissolved in 5ml of 2-butanone (Fujifilm Wako Pure Chemical Industries, Ltd.) and 4.56g (5.1mmol, Apollo Scientific Co., Ltd.) of sodium tetrakis[3,5-bis(trifluoromethyl)phenyl]borate dissolved in 5mL of 2-butanone were dropped into the Erlenmeyer flask and stirred at room temperature for 30 minutes. After stirring, the reaction product was washed once with 50ml of saturated aqueous sodium bicarbonate solution, three times with 50ml of water, and once with saturated saline, and the organic layer was dried over 20g of sodium sulfate. The organic solvent was then removed by distillation, and the residue was dried under reduced pressure to obtain 4.22 g (yield 69%) of N,N-dimethyl,N-(4-methoxybenzyl)anilinium tetrakis[3,5-bis(trifluoromethyl)phenyl]borate.
[0117] [Compound Identification] The compound obtained above 1 H NMR spectra were measured using an NMR (JNM-ECX400II, manufactured by JEOL Ltd.) The spectral data for each compound are shown below. 4-Methoxybenzyl iodide (400MHz, CDCl3) , δ:3.79(s,3H),4.48(s,2H),6.82(d,2H,J=8.8Hz),7.32(d,2H,J=8.8Hz) N,N-Dimethyl,N-(4-methoxybenzyl)anilinium iodide (400MHz,CD3OD), δ:3.64(s,6H),3.77(s,3H),4.98(s,2H),6.84(dt,2H,J=8.8,2.4Hz),7.01(dt,2H,J=8.8,2.4Hz),7.06~7.62(m,3H),7.75~7.77(m,2H) ·N,N-Dimethyl,N-(4-methoxybenzyl)anilinium·tetrakis[3,5-bis(trifluoromethyl)phenyl]borate (400MHz,CD3OD), δ:3.60(s,6H),3.75(s,3H),4.92(s,2H),6.83(dt,2H,J=8.8,2.4Hz),6.97(dt,2H,J=8.8,2.4Hz),7.58~7.61(m,15H),7.71~7.73(m,2H)
[0118] <Synthesis Example 2> (Synthesis of N,N-dimethyl,N-(4-methoxybenzyl)anilinium tetrakis(pentafluorophenyl)borate) N,N-Dimethyl,N-(4-methoxybenzyl)anilinium tetrakis(pentafluorophenyl)borate was synthesized in the same manner as in Synthesis Example 1, except that Step 3A was changed to the following Step 3B.
[0119] [Process 3B] A 200 ml Erlenmeyer flask with a magnetic stirrer and a stirrer tip was prepared, and 50 ml of ethyl acetate was mixed with 1.85 g (5.0 mmol) of N,N-dimethyl,N-(4-methoxybenzyl)anilinium iodide. 38.61 g (5.0 mmol) of a 10% solution of sodium tetrakis(pentafluorophenyl)borate was added dropwise to the Erlenmeyer flask and stirred at room temperature for 30 minutes. After stirring, the reaction product was washed once with 50 ml of saturated aqueous sodium bicarbonate solution, three times with 50 ml of water, and once with saturated saline, and the organic layer was dried with 20 g of sodium sulfate. The organic solvent was then distilled off and the residue was dried under reduced pressure to obtain 2.16 g (47% yield) of N,N-dimethyl,N-(4-methoxybenzyl)anilinium tetrakis(pentafluorophenyl)borate.
[0120] [Compound Identification] The compound obtained above 1 The H NMR spectrum was measured using an NMR (JNM-ECX400II, manufactured by JEOL Ltd.) The spectral data of the compound are shown below. ·N,N-Dimethyl,N-(4-methoxybenzyl)anilinium·tetrakis(pentafluorophenyl)borate (400MHz,CD3OD), δ:3.60(s,6H),3.75(s,3H),4.92(s,2H),6.83(dt,2H,J=8.8,2.4Hz),6.97(dt,2H,J=8.8,2.4Hz),7.58~7.63(m,3H),7.69~7.73(m,2H)
[0121] <Synthesis Example 3> (Synthesis of thermoplastic resin P-1) In a 3000mL three-neck flask equipped with a Dimroth condenser, a calcium chloride tube, and a Teflon (registered trademark) stirring rod connected to a stirring motor, 45g of 4,4'-(9-fluorenylidene)-diphenol (Sigma-Aldrich Japan Co., Ltd.) and 50g of 3,3',5,5'-tetramethylbiphenol diglycidyl ether (product name: YX-4000H, Mitsubishi Chemical Co., Ltd.) were dissolved in 1000mL of N-methylpyrrolidone to prepare a reaction solution. 21g of potassium carbonate was added to this reaction solution, and the mixture was stirred for 3 hours while being heated to 110°C with a mantle heater. The reaction solution after stirring was dropped into a beaker containing 1000mL of methanol, and the precipitate formed by suction filtration was collected by filtration. The collected precipitate was further washed three times with 300mL of methanol to obtain 75g of phenoxy resin P-1. The molecular weight of the obtained phenoxy resin P-1 was measured using a high-performance liquid chromatograph (Tosoh Corporation, GP8020, column: Hitachi High-Tech Fielding Corporation Gelpack GL-A150S and GLA160S, eluent: tetrahydrofuran, flow rate: 1.0 mL / min), and the polystyrene equivalent molecular weights were Mn=15769, Mw=38045, and Mw / Mn=2.413.
[0122] <Production Example 1> (Preparation of conductive particles) A layer of nickel was formed on the surface of the cross-linked polystyrene particles to a thickness of 0.15 μm, thus obtaining conductive particles with an average particle size of 3.3 μm, a maximum particle size of 3.5 μm, and a specific gravity of 2.7.
[0123] <Experimental Examples A1 to A6> (Preparation of adhesive film) Varnish-like adhesive compositions X1 to X6 were prepared by mixing the components shown in Table 1 in the amounts (unit: parts by mass) shown in the table with 2-butanone (methyl ethyl ketone). The amount of each component in the table represents the amount of non-volatile matter. The amounts of the thermal cationic polymerization initiators were mixed so that the mass per unit substance was equal.
[0124] [Table 1]
[0125] Each of the adhesive compositions X1 to X6 was applied onto a substrate (PET film), and dried to remove the organic solvent, thereby forming adhesive films X1 to X6 having a thickness of 10 μm on the substrate.
[0126] (DSC evaluation) For the adhesive films X1 to X6, DSC measurements were carried out from 50°C to 300°C under a nitrogen (N2) atmosphere at a temperature rise rate of 10°C / min using a PerkinElmer differential scanning calorimeter (product name: DSC Q1000), and the heat generation start temperature [°C], peak top temperature [°C], heat generation end temperature [°C], and heat generation amount [J / g] were calculated. The results are shown in Table 2 and Figures 4 to 6.
[0127] [Table 2]
[0128] As shown by the comparison between Experimental Example A1 and Experimental Example A2, and the comparison between Experimental Example A3 and Experimental Example A4, it was confirmed that the DSC heat generation onset temperature and peak top temperature were lowered by using an alicyclic epoxy compound as the cationic polymerizable compound and an onium salt having tetrakis[3,5-bis(trifluoromethyl)phenyl]borate anion as the thermal cationic polymerization initiator. In addition, the comparison between Experimental Example A5 and Experimental Example A6 confirmed that the above-mentioned lowering of the temperature is an effect that occurs specifically when an alicyclic epoxy compound is used as the cationic polymerizable compound.
[0129] (Evaluation of cured properties) The cured properties of adhesive films X3 to X4 were evaluated. Specifically, a plurality of adhesive films were prepared, laminated to a thickness of 200 μm, and heated in an oven at 180 ° C for 1 hour to prepare a cured film for evaluation. Then, the cured film was subjected to DMA measurement from 50 ° C to 300 ° C at a heating rate of 10 ° C / min using a dynamic viscoelasticity device (product name: RSA-3) manufactured by TA Instruments Japan Co., Ltd., and the storage modulus at 250 ° C was obtained. In addition, the cured film was subjected to TG / DTA measurement from 100 ° C to 400 ° C at a heating rate of 20 ° C / min using a TG / DTA measurement device (product name: TG / DTA7200) manufactured by SII Nano Technology Co., Ltd., and the 5% weight loss onset temperature was obtained. The results are shown in Table 3 and Figures 7 to 8.
[0130] [Table 3]
[0131] Comparing Experimental Example A3 with Experimental Example A4, it was confirmed that the heat resistance was improved (the storage modulus was improved and the 5% weight loss onset temperature was also increased) by using an alicyclic epoxy compound and an oxetane compound as the cationic polymerizable compound and an onium salt having a tetrakis[3,5-bis(trifluoromethyl)phenyl]borate anion as the thermal cationic polymerization initiator.
[0132] <Experimental Examples B1~B5> (Preparation of adhesive for circuit connection) Varnish-like adhesive compositions (first adhesive compositions) Y1 to Y4 for forming a first adhesive layer and varnish-like adhesive compositions (second adhesive compositions) Z1 to Z4 for forming a second adhesive layer were prepared by mixing each of the components shown in Tables 4 and 5 in the amounts (unit: parts by mass) shown in the tables with 2-butanone (methyl ethyl ketone). The amount of each component in the tables represents the amount of non-volatile matter. The amounts of the thermal cationic polymerization initiators were mixed so that the mass per unit substance amount was equal.
[0133] [Table 4]
[0134] [Table 5]
[0135] An adhesive film for circuit connection was produced using the first adhesive composition and the second adhesive composition in the combination shown in Table 6. Specifically, the second adhesive composition was first applied onto a substrate (PET film), dried, and the organic solvent was removed to form a second adhesive layer having a thickness of 11 μm on the substrate. Next, the first adhesive composition was applied onto the second adhesive layer, dried, and the organic solvent was removed to form a first adhesive layer having a thickness of 7 μm on the second adhesive layer. In this way, an anisotropic conductive film (adhesive film for circuit connection) was produced in which the substrate, the second adhesive layer, and the first adhesive layer were laminated in this order.
[0136] (Preparation of connection structure) As the first circuit member, a glass substrate with wiring was prepared in which a wiring pattern (pattern width: 19 μm, space between electrodes: 5 μm) of AlNd (100 nm) / Mo (50 nm) / ITO (100 nm) was formed on the surface of an alkali-free glass substrate (OA-11, manufactured by Nippon Electric Glass Co., Ltd., outer dimensions: 38 mm × 28 mm, thickness: 0.3 mm). As the second circuit member, an IC chip (outer dimensions: 0.9 mm × 20.3 mm, thickness: 0.3 mm, bump electrode size: 70 μm × 12 μm, space between bump electrodes: 12 μm, bump electrode thickness: 8 μm) in which bump electrodes were arranged in a staggered pattern in two rows was prepared.
[0137] The anisotropic conductive film prepared above was placed on the first circuit member so that the first adhesive layer was in contact with the surface of the first circuit member on which the wiring was formed. Using a thermocompression bonding device (LD-06, manufactured by Ohashi Manufacturing Co., Ltd.) consisting of a stage made of a ceramic heater and a tool (8 mm x 50 mm), the anisotropic conductive film was bonded at 50°C and 0.98 MPa (10 kgf / cm 2 ) for 2 seconds, the anisotropic conductive film was attached to the first circuit member. Then, the release film on the side of the anisotropic conductive film opposite to the first circuit member was peeled off. Next, the circuit electrodes of the first circuit member and the bump electrodes of the second circuit member were aligned, and then, using a heat tool of 8 mm x 45 mm, they were heated and pressed on a base heated to 80°C via a PTFE sheet having a thickness of 50 μm as a buffer material. The mounting temperature (the measured maximum temperature of the anisotropic conductive film) was 115°C or 125°C, the heating time was 5 seconds, and the pressure during pressing (the pressure converted into the area at the bump electrode) was 60 MPa. In this way, the second adhesive layer of the anisotropic conductive film was attached to the second circuit member, and a connection structure was obtained.
[0138] <Evaluation of connection structures> The connection resistance of the connection structure produced above was measured by a four-terminal measurement method initially (immediately after production) and after a high-temperature, high-humidity test to evaluate the electrical conductivity between the opposing electrodes. Specifically, the connection resistance was measured at 14 points using a multimeter (MLR21, manufactured by Kusumoto Chemicals Co., Ltd.), and the maximum connection resistance values (maximum resistance values) were compared. The high-temperature, high-humidity test was performed by storing the connection structure for 250 hours in a constant temperature and humidity chamber at a temperature of 85°C and a humidity of 85% RH. The evaluation results are shown in Table 6.
[0139] In addition, the interface between the first circuit member and the circuit connection portion (cured product of the anisotropic conductive film) was observed using an FPD / LSI inspection microscope (Nikon Instech Corporation, ECLIPSE L300ND) from the opposite side of the adhesive surface of the first circuit member to the anisotropic conductive film at the initial stage (immediately after fabrication) of the connection structure and after the high temperature and high humidity test to confirm the presence or absence of peeling. The interface between the first circuit member and the circuit connection portion where no peeling occurred was rated A (good adhesion), and the interface where peeling occurred was rated B (poor adhesion). The evaluation results are shown in Table 6.
[0140] [Table 6] [Explanation of symbols]
[0141] 1...adhesive film for circuit connection, 1A...first adhesive layer, 1B...second adhesive layer, 2A, 2B...adhesive component, 3A...conductive particles, 4...first circuit member, 5...second circuit member, 6...circuit connection portion, 10...connection structure, 41...first circuit board, 42...first electrode, 51...second circuit board, 52...second electrode.
Claims
1. Contains a cationic polymerizable compound, a thermal cationic polymerization initiator, and conductive particles; the cationically polymerizable compound comprises an alicyclic epoxy compound, The adhesive for circuit connection, wherein the thermal cationic polymerization initiator contains an onium salt having an anion represented by the following formula (1): 【Chemistry 1】
2. 2. The adhesive for circuit connection according to claim 1, wherein the thermal cationic polymerization initiator contains, as the onium salt, at least one compound selected from the group consisting of sulfonium salts and ammonium salts.
3. The adhesive for circuit connection according to claim 1 or 2, which is in the form of a film.
4. A first adhesive layer and a second adhesive layer laminated on the first adhesive layer, The adhesive for circuit connection according to claim 3 , wherein the first adhesive layer contains the cationically polymerizable compound, the thermal cationic polymerization initiator, and the conductive particles.
5. a first circuit member having a first electrode, a second circuit member having a second electrode, and a circuit connection portion disposed between the first circuit member and the second circuit member, electrically connecting the first electrode and the second electrode to each other; A connection structure, wherein the circuit connection portion comprises a cured product of the circuit connection adhesive according to any one of claims 1 to 4.
6. 13. A method for manufacturing a connection structure, comprising the steps of: interposing the circuit connection adhesive according to any one of claims 1 to 4 between a first circuit member having a first electrode and a second circuit member having a second electrode; and thermocompression bonding the first circuit member and the second circuit member to electrically connect the first electrode and the second electrode to each other.
Citation Information
Patent Citations
Connecting device for electronic parts
JP1989251787A
Polymerizable composition and its cured substance
JP1998001507A
Diaryliodonium salt type reaction initiator, energy-ray- curing composition containing the same and cured product of its composition
JP2000007684A
Adhesive composition, circuit connecting material, connector and connection method of circuit member, and semiconductor device
JP2011111557A
Thermopolymerization initiator system and adhesive composition
JP2011116977A